2021
DOI: 10.1016/j.aninu.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean raffinose on growth performance, digestibility, humoral immunity and intestinal morphology of growing pigs

Abstract: There are appreciable does of raffinose in soybean, but the impacts of raffinose on pigs are poorly investigated. We used 2 experiments to investigate the influence of soybean raffinose on growth performance, digestibility, humoral immunity and intestinal morphology of growing pigs. In Exp. 1, a total of 30 crossbred (Duroc × Landrace × Yorkshire) barrows (21.93 ± 0.43 kg) were randomly divided into 3 groups, and were fed with the control diet, the control diets supplemented with 0.2% and 0.5% raffinose, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, hypersecretion of these cytokines can induce multiple organ dysfunction syndromes ( 32 ). While TNF-α, IL-1β, and IL-6 are pivotal pro-inflammatory cytokines that trigger immune responses, IL-10 is an anti-inflammatory cytokine that inhibits immune responses ( 33 ). In this study, IL-1β and TNF-α concentrations were linearly diminished, whereas IL-10 concentration was linearly augmented with the increasing doses of LM1 supplementation in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypersecretion of these cytokines can induce multiple organ dysfunction syndromes ( 32 ). While TNF-α, IL-1β, and IL-6 are pivotal pro-inflammatory cytokines that trigger immune responses, IL-10 is an anti-inflammatory cytokine that inhibits immune responses ( 33 ). In this study, IL-1β and TNF-α concentrations were linearly diminished, whereas IL-10 concentration was linearly augmented with the increasing doses of LM1 supplementation in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a negative correlation between raffinose and GE ( Figure 1 ). It had been illustrated that raffinose could reduce nutrient digestibility and the growth performance of animals ( Zeng et al., 2021 ). Furthermore, the DM and GE digestibility of combined soybean meal 1 were significantly decreased compared with other soybean meals.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that RFOs are responsible for increasing digesta viscosity, which interferes with the digestion of nutrients. Zeng et al (2021) observed that dietary raffinose (0.2 and 0.5%) could reduce pig growth performance by decreasing feed intake and nutrient digestibility, while improving intestinal morphology and negatively affecting immunity. Reduction of oligosaccharide contents in soybean meals could increase the amount of soybean proteins in diets.…”
Section: Discussionmentioning
confidence: 99%
“…Fernando et al (2010) found that raffinose could modulate intestinal microbial composition and promote intestinal health in humans. Moreover, dietary RFO supplementation significantly reduced the production of odour compounds by modulating the caecal microbial community (Zeng et al, 2021). A single dose of RFOs delivered in ovo on day 12 of egg incubation beneficially modulated chick body systems and did not affect optimal performance (Stadnicka et al, 2020).…”
Section: Introductionmentioning
confidence: 97%